Analysis of Creative Thinking Skill in Solving Mathematical Problems Viewed from the Types of Personality - Anggorowati, Wening; Kariadinata, Rahayu; Widiastuti A., T. Tutut (KnE Social Sciences, 2024)
Creative thinking skills are part of the student’s thinking process in solving math problems. Each student has a different thought process according to their personality, so needed suitable learning model for each type of integration. One of the personality type that can be used to review students creative thinking skills is the Keirsey personality type. The purpose of this research is to obtain a description of student personality types based on Keirsey personality test results and creative thinking skills of students in solving mathematical problems on personality types Guardian, Artisan, Rational, and Idealist. The research subjects were students of class X MIPA 1 in one of the senior high schools in Bandung by purposive sampling. This research is descriptive-qualitative research. The results showed that subjects with Guardian personality types became the majority in the class and students with Idealist personality types became the minority. Then based on the results of the analysis, students with Guardian personality types meet indicators of fluency, novelty, and elaboration; Artisans meet indicators of fluency and novelty; Idealists meet indicators of fluency and novelty; and Rational meet all indicators of creative thinking skills, namely fluency, flexibility, novelty and elaboration. By knowing the student’s personality type, it is expected to be a reference in teaching methods in order to improve student creative thinking skills. Keywords: creative thinking skill, solving mathematical problems, types of personality